Evaluation of referral system in Thaba Nchu Health sub-district - Mojaki, Monnapule Eric (My University, 2010)
Introduction: South African health system embraces the District Health System model. 1 District health system includes health stations or posts, other health care facilities such as private health practitioners, community based organisations. primary health care clinics and district hospitals. District hospitals provide first level of outpatient or inpatient care for patients who have been referred by their primary care providers. District hospitals usually provide 24 hour care and are integrated into district health system. The above set up is similar in Thaba Nchu Health sub district where Dr.J.S.Moroka Hospital (DJSMH) is a district hospital and therefore, a referral point for 11 clinics within Thaba Nchu sub district and 4 clinics from the neighbouring sub district. In addition, there are 5 general practitioners rooms within Thaba Nchu sub district. The DJSMH is overburdened with increasingly high caseload. Main Aim: To evaluate the referral system in the Thaba Nchu Health Sub-district, Free State Province in terms of the factors that influences its function. Methodology: This was a descriptive study undertaken at Dr.J.S.Moroka Hospital Outpatient and Casualty departments. The study included review of routinely collected hospital information on patients’ records and registers. No intervention was done for this study. Results : The referral system within the sub district is not fully functional. Most patients that are seen in the DJSMH are self referrals. The case load and work load of the two designated areas could be reduced if most of the patients could have started and be seen at the primary health care clinics. Although the registers were helpful in collecting information, the documentation on patients’ records by health workers is not consistent; it is poor and need to be improved. The records have shown that the personnel are doing little in strengthening the referral system within the district. Conclusion: This study was the first of its kind to be done in this DJSMH. Although there are good practices with regard to referral system within the Thaba Nchu subdistrict and Dr. J.S Moroka Hospital, much still has to be done to ensure that the primary health care clinics and hospitals are effectively functioning in rendering services relevant to each level of care. More patients seen in the DJSMH are self referrals that could be managed at the primary health care clinics. The interventions recommended in this study will assist in strengthening the delivery of district health care system and in particular improve the referral system within the sub district.
MPH, Faculty of Health Sciences, University of the Witwatersrand
Keywords: medical referrals; Thaba Nchu, Free State